Molecular cloning and functional verification of chalcone synthase genes from cassava (Manihot esculenta Crantz) in defense against Tetranychus cinnabarinus infestation - Yanni Yang; Kaiwen Zheng; Limei Gao; Yakang Hu; Cuixia Liu; Fei Li; Ming Liu (PLoS ONE, 2025)
Secondary metabolites such as flavonoids play an important role in protecting plants from biological agents such as fungi, pathogens, bacteria and pests. Chalcone synthase (CHS) is the first enzyme in the plant flavonoid biosynthesis pathway, and is also a key enzyme and rate-limiting enzyme in the secondary metabolite production pathway, which has very important physiological significance in plants. Despite extensive characterization in various plants, the functions of CHS in cassava remain unknown. Here, MeCHS1, MeCHS3 and MeCHS5 genes from Manihot esculenta Crantz were isolated and functionally analyzed. The results showed that the over-expression of the three MeCHSs were beneficial to control the further reproduction of Tetranychus cinnabarinus. At the same time, the transfer of MeCHS1, MeCHS3 and MeCHS5 genes can promote the synthesis of more secondary metabolites in Arabidopsis thaliana. Heterologous expression in A. thaliana indicated the presence of different expression levels of the three MeCHSs in defense against T. cinnabarinus infestation. Correlation analysis showed that the expression of MeCHSs were positively correlated with the synthesis of secondary metabolites, and negatively correlated with survival rate of T. cinnabarinus. These results indicate that the different expression levels of MeCHS genes lead to the difference in the synthesis of secondary metabolites, and thus the resistance of A. thaliana to T. cinnabarinus is also different.